2015
DOI: 10.1007/s00338-015-1316-9
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive genetic structure at different geographic scales in the coral-excavating sponge Cliona vermifera (Hancock, 1867) in the Mexican Pacific

Abstract: Cliona vermifera is one of the most abundant excavating sponges in Mexican coral reefs, and represents a potential threat to their health. It appears to have limited dispersal potential, but, paradoxically, it is widespread over much of the 2000 km of Mexican Pacific waters, suggesting mechanisms of long-distance dissemination. Despite its ecological importance, nothing is known about its patterns of genetic structure and connectivity in space and time. In this study, we assess levels of genetic structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…For example, León-Pech et al 65 found a minimum of 0.2% divergence within C. vermifera, and we detected at least some sequence variability in all species compared except C. yorkin. Alternative markers commonly used in phylogenetic and taxonomic studies of sponges include nuclear markers such as ITS and 28S loci of the ribosomal RNA (rRNA) region 66 , with the former being common in phylogeographic studies due to their higher degree of intraspecific variability 65,67 (but see Wörheide et al 45 ). The lack of variability across the whole mitochondrial genome and ribosomal genes examined here could be caused by common maternal inheritance within C. patera.…”
Section: Discussionsupporting
confidence: 63%
“…For example, León-Pech et al 65 found a minimum of 0.2% divergence within C. vermifera, and we detected at least some sequence variability in all species compared except C. yorkin. Alternative markers commonly used in phylogenetic and taxonomic studies of sponges include nuclear markers such as ITS and 28S loci of the ribosomal RNA (rRNA) region 66 , with the former being common in phylogeographic studies due to their higher degree of intraspecific variability 65,67 (but see Wörheide et al 45 ). The lack of variability across the whole mitochondrial genome and ribosomal genes examined here could be caused by common maternal inheritance within C. patera.…”
Section: Discussionsupporting
confidence: 63%
“…Phylogeography studies of marine organisms have been traditionally based on mitochondrial genes, in particular, the COI barcode marker (Avise 2009 ). However, the several partitions of COI used up to now for phylogeography studies seem to be extraordinarily conserved in the Phylum Porifera (Duran et al 2004a ; Wörheide et al 2005 ; Uriz and Turon 2012 ; but see León-Pech et al 2015 ) and thus are poorly informative for analyses of population genetics at ecological time scales. Conversely, hypervariable molecular markers such as microsatellites have proved suitable for studying recent historical events in demography and population genetics of sponges (see Uriz and Turon 2012 for a review; Chaves-Fonnegra et al 2015 ) and may help in tracking the expansion patterns of recently introduced species.…”
Section: Introductionmentioning
confidence: 99%
“…Although mitogenome sequences were only obtained from four individuals, the low nucleotide diversity we observed in organisms spanning the whole latitudinal range of our sampling area (~900 km, which is almost the entire species distribution) indicates that protein‐coding mitochondrial markers provide almost no resolution for population genetic studies for D. antarctica . This extremely low variability in mitochondrial markers is not uncommon in sponges because COI has traditionally showed relatively low genetic variation at both intra‐ and interspecific levels (e.g., Dailianis, Tsigenopoulos, Dounas, & Voultsiadou, ; León‐Pech, Cruz‐Barraza, Cruz‐Barraza, Carballo, Calderon‐Aguilera, & Rocha‐Olivares, ; Riesgo et al, ; Setiawan et al, ; Taboada et al, ) with just a few exceptions (DeBiasse et al, ; Duran & Rützler, ; López‐Legentil & Pawlik, ; Xavier et al, ), probably due to slower rates of mitochondrial genome evolution and/or the presence of active mitochondrial repair mechanisms (Huang, Meier, et al, ).…”
Section: Discussionmentioning
confidence: 99%